2005
DOI: 10.2136/sssaj2004.0174
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Vadose Zone Water Flux from Multi‐Functional Heat Pulse Probe Measurements

Abstract: cluding empirical and tracer methods, were presented by Tyler et al. (1999) and Flint et al. (2002). A major A small multi-functional heat pulse probe (MFHPP) was applied advantage of the MFHPP technique is that the water to further develop measurement methodologies to improve on water flux estimations for unsaturated soils. The temperature responses of flux can be estimated indirectly from heat transport by four thermistors surrounding a central heater in a 2.7-cm diam. probe convection, without the need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 38 publications
3
58
0
Order By: Relevance
“…TPHPS have been used to measure the advective liquid heat flux in mineral soils [Mori et al, 2005;Ochsner et al, 2005;Ren et al, 2000] but have not, to our knowledge, been previously used in peat soils.…”
Section: Introduction and Aim Of The Researchmentioning
confidence: 99%
“…TPHPS have been used to measure the advective liquid heat flux in mineral soils [Mori et al, 2005;Ochsner et al, 2005;Ren et al, 2000] but have not, to our knowledge, been previously used in peat soils.…”
Section: Introduction and Aim Of The Researchmentioning
confidence: 99%
“…The experimentally derived Equation determined in this study, however, conflicts with Equation , which was deduced theoretically by de Marsily () and showed a linear relation between the thermal dispersion coefficient and water flux density, and with that found by Rau et al (), which showed a square relation between two parameters. Mori et al () concluded that thermal dispersion was almost independent of J w for a Tottori Dune sand. Compared to the studies mentioned above for which heat dispersion was determined theoretically, indirectly or on an ideal porous media (e.g., Tottori Dune sand), the current study acquired the heat dispersion coefficient experimentally using natural soils with a non‐uniform particle‐size distribution and focused on relatively small water flow velocities.…”
Section: Resultsmentioning
confidence: 99%
“…Ren, Noborio, and Horton () combined heat‐pulse with TDR technology to develop a thermo–time domain reflectometry (thermo–TDR) probe, which can estimate simultaneously soil thermal properties with a heat‐pulse probe and soil hydraulic and solute transport model parameters with TDR technology under the same measurement volume. Thus, thermo–TDR allows simultaneous analysis of the nature of coupled flow, heat and solute transport in soil (Mori et al, ; Mortensen, Hopmans, Mori, & Simunek, ), which makes it possible to explore the relation between thermal and solute dispersion. Our previous study showed experimentally that thermal dispersion occurred in water‐saturated soils with one‐dimensional water flow and fluxes in the range of 1.2 to 21.6 cm hour −1 (Lu, Ren, & Gong, ), which established an experimental basis for further comparison of thermal and solute dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…11 Modified three-phase unit cell based on the lumped parameter model [35] and its decomposition into serial and parallel layers (I-III) of thermal resistors sensitive to contacts. As the microscopy instruments and the observation technologies are also well developed now, the image mapping has become a highly powerful tool for approaching the real structures in more geometric details such as the element shapes, orientations and connections, on the materials properties [84,85]. Better reconstruction processes have been used to generate two-phase [86,87] and multi-phase [88,89] random structures of porous materials based on the digital micro-tomographic information and statistical correlation functions.…”
Section: Methodsmentioning
confidence: 99%